Tree-piping termites and growth and survival of host trees in savanna woodland of north Australia - Werner, Patricia A.; Prior, Lynda D. (Journal of tropical ecology, 2007)
Most trees in the eucalypt savannas of Australia have hollow cores, or pipes, caused by termite activity, yet little is known about their effect on tree growth or survival. Five hundred and forty-one trees with known growth and survival histories were cored to determine pipe diameters in wooded savanna of Kakadu National Park, north Australia. Generalized linear modelling and multi-model inference was used to analyse frequency and degree of piping relative to initial tree diameter at breast height (dbh), eco-taxonomic group or species of eucalypt. Growth (dbh increment) and survival (4 y) were analysed relative to initial tree size, pipe ratio (pipe diameter:dbh) and eco-taxonomic group. The frequency of piping was strongly dependent on dbh, increasing with size of tree, and was highest in eucalypts. Growth and survival of eucalypts increased with tree diameter and decreased with pipe ratio. For example, from modelled data, 10-cm-diameter trees without pipes grew 0.14 cm y−1 with 85% survival vs. 10-cm trees with pipe ratios of 0.60 which had near-zero growth and only 46% survival. Comparing 40-cm-diameter trees without pipes to those having pipe ratios of 0.80, growth was 0.22 vs. 0.05 cm y−1, with little difference in survival, 97–99%, respectively. Contrary to the suggestion that tree hollows are an adaptive trait whereby trees benefit by the release of nutrients, in the north Australian eucalypt savannas the net effect of termite piping on individual tree growth and survival was negative.